2011
DOI: 10.1038/nchembio.686
|View full text |Cite
|
Sign up to set email alerts
|

Arl2-GTP and Arl3-GTP regulate a GDI-like transport system for farnesylated cargo

Abstract: Lipidated Rho and Rab GTP-binding proteins are transported between membranes in complex with solubilizing factors called 'guanine nucleotide dissociation inhibitors' (GDIs). Unloading from GDIs using GDI displacement factors (GDFs) has been proposed but remains mechanistically elusive. PDEδ is a putative solubilizing factor for several prenylated Ras-subfamily proteins. Here we report the structure of fully modified farnesylated Rheb-GDP in complex with PDEδ. The structure explains the nucleotide-independent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
359
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 238 publications
(387 citation statements)
references
References 46 publications
20
359
1
2
Order By: Relevance
“…Finally, protein chaperones may exist that facilitate removal of prenylated βγ from membranes. Many such proteins are known to act on prenylated small GTPases (20)(21)(22), and phosducin is known to facilitate βγ translocation in photoreceptors by diminishing its membrane partitioning (23,24). It is unknown whether chaperones regulate βγ translocation in other cell types.…”
Section: Same Residues That Determine βγ-Translocation Rates Directlymentioning
confidence: 99%
“…Finally, protein chaperones may exist that facilitate removal of prenylated βγ from membranes. Many such proteins are known to act on prenylated small GTPases (20)(21)(22), and phosducin is known to facilitate βγ translocation in photoreceptors by diminishing its membrane partitioning (23,24). It is unknown whether chaperones regulate βγ translocation in other cell types.…”
Section: Same Residues That Determine βγ-Translocation Rates Directlymentioning
confidence: 99%
“…The structures showed how the binding of Arl2 (or Arl3) induces the hydrophobic pocket to narrow such that the C-terminal farnesylated end of the protein gets squeezed out of the pocket. 41 A structure of PDE6d and a geranylgeranylated peptide (with 4 isoprenyl groups rather than 3 compared to farnesylated peptides) from the a' subunit of PDE6 could also be solved. It shows that the C20 modification can bind into the same pocket such that the extra 5 residues of the geranylgeranyl group extend the pocket by 5 C atoms.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
“…Based on studies with Ras or Rheb, 2 prenylated proteins that reside in cytoplasmic membranes, it was assumed that the nature of cargo does not influence the interaction with PDE6d. 41 It was also shown that the affinity is dictated by only the last few C-terminal residues of these proteins, since C-terminal peptides of 6-7 residues bind with the same affinity as the full-length protein. 34 However, investigation of the interaction of the ciliary protein inositol 5 0 phosphatase (INPP5E) with PDE6d revealed a difference in the binding affinity when compared to the non-ciliary proteins Ras and Rheb.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
See 2 more Smart Citations